2015
DOI: 10.1515/ijfe-2014-0266
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Improving the Performance of Cabinet Solar Dryer Using Computational Fluid Dynamics

Abstract: In this study, a new approach for numerically modeling of an entire cabinet solar dryer is proposed. Collector, drying chamber and chimney are the three principle sections considered in the present modeling. The collector section containing a cover and an absorber plate is modeled applying energy and fluid flow equations to obtain temperature distribution inside the collector. Due to the non-linear behavior of the governing equations as well as variety of effective variables, an iterative method is employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Holes at its base and at upper parts of the sides allow buoyancy driven moisture removal (Tiwari and Ghosal, 2005;Chua and Chou, 2003). That can be enhanced by the addition of a chimney (Ghaffari and Mehdipour, 2015). Adequate moisture removal is essential both for the drying process and to prevent insolation transmission being reduced by moisture condensating inside the glass cover.…”
Section: Direct Passive Solar Dryersmentioning
confidence: 99%
“…Holes at its base and at upper parts of the sides allow buoyancy driven moisture removal (Tiwari and Ghosal, 2005;Chua and Chou, 2003). That can be enhanced by the addition of a chimney (Ghaffari and Mehdipour, 2015). Adequate moisture removal is essential both for the drying process and to prevent insolation transmission being reduced by moisture condensating inside the glass cover.…”
Section: Direct Passive Solar Dryersmentioning
confidence: 99%
“…Ghaffari and Mehdipour (2015) presented a novel modeling and optimizing method for indirect natural convection solar dryers by the use of thermodynamic equations and a CFD model. It was observed that by adding a few baffles in the lower part of the drying chamber and directing hot air toward the products, efficiency was increased and drying time was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Although cannot replace experiments fully, simulation by CFD proved to be a reliable optimization tool to reduce the time required by the experiments. CFD analysis can also help to understand the performance of the system under varying parameters (Amanlou & Zomorodian, 2010;Ghaffari & Mehdipour, 2015). Mirade (2003) reported the simulation results for twodimensional meat dryer to recognize air flow homogeneity over the product and inferred that ventilation cycles play an important role in drying.…”
Section: Introductionmentioning
confidence: 99%